Single port robotic transvesical repair of bladder neck contracture - Courtney Yong; Ethan Ferguson (Urology Video Journal)
Objective: The single port robotic transvesical approach has been used for simple and radical prostatectomy. This video shows a single port, transvesical approach to a bladder neck contracture repair. Patients and surgical procedure: The patient is a 66-year-old male with a history of BPH and two prior TURPs. He developed a bladder neck contracture and underwent an incision of the bladder neck. However, his symptoms returned, and he went into retention requiring indwelling catheterization. Cystoscopy showed a short, 16Fr bladder neck contracture. He elected for a robotic bladder neck contracture repair. The repair was performed with the single port robot using the transvesical approach. We made a 3 cm suprapubic incision, accessed the space of Retzius through the midline, filled the bladder, and made a small cystotomy. The access port was placed directly into the bladder. We dissected around the contracture and carried the dissection distally toward the urethra. We excised the contracture at the verumontanum. The urothelium was advanced to the urethra using two running 3–0 stratafix sutures. A catheter was place prior to closure of the bladder and fascia. Results: The procedure time was 106 min with 55 min of console time and little blood loss. Pathology showed urothelium with inflammation and fibrosis. The patient was discharged with an indwelling catheter, which was removed on postoperative day 6. The patient was able to void to completion. At one month follow up, he was continent. Cystoscopy showed a patent, healing bladder neck and healing cystotomy closure. At around 9 months follow up, the patient was voiding well with Qmax 17.3 ml/s and PVR 3 ml. He has urinary frequency and urgency managed with oral medications. Conclusions: The transvesical single port robotic approach is a minimally invasive option for repair of bladder neck contracture. While this patient had a short stricture, longer or denser strictures may require more complex reconstruction such as Y-V-plasty or even prostatectomy. However, the single port robot would also facilitate these intraoperative adjustments.